2018
DOI: 10.1149/2.0151803jss
|View full text |Cite
|
Sign up to set email alerts
|

Low Frequency Noise Analysis of Impact of Metal Gate Processing on the Gate Oxide Stack Quality

Abstract: A review is given about the impact of the metal gate (MG) in a High-κ/Metal Gate (HKMG) stack on the quality and defectivity of the dielectric, assessed by low-frequency (LF) noise spectroscopy. In a first part, processing aspects are discussed, like, the thickness of the MG and the implementation of a gate-last approach. In the latter case, it is shown that both the cleaning (or dummy gate removal), the growth of the interfacial SiO 2 layer (chemical versus thermal) and a post-HfO 2 -deposition heat or SF 6 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…itself as the impact of this parameter on the 1/f noise performance has recently been reviewed by the authors. [21][22][23]…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…itself as the impact of this parameter on the 1/f noise performance has recently been reviewed by the authors. [21][22][23]…”
mentioning
confidence: 99%
“…itself as the impact of this parameter on the 1/f noise performance has recently been reviewed by the authors. [21][22][23] Trap density.-In the case that the noise is dominated by carrier number fluctuations (CNF or n), i.e., capturing/emission of carriers by/from traps in the dielectric, the trap density N ot can be calculated from the 1/f noise PSD using: 15,16,24…”
mentioning
confidence: 99%
“…[5][6][7][8] As is well known, the gate oxide quality and reliability strongly depend on the type of high-k material and the interfacial oxide layer. [9] The measuring of low-frequency noise also known as 1/ f noise is usually used as a non-destructive technique for evaluating the quality of the oxide-semiconductor interface and channel layers. [10,11] Many studies reported in the literature have pointed out that carrier number fluctuation (∆n) and correlated mobility fluctuation (∆µ) are the main physical mechanisms that give rise to the 1/ f noise phenomena.…”
Section: Introductionmentioning
confidence: 99%